Das Netzwerk der Montaigus zwischen Okzident und Orient - Burgtorf, Jochen (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2015)
During the .rst half of the thirteenth century, the noble family of Montaigu from Auvergne featured a set of brothers who became masters of the Order of the Hospital (Garin) and that of the Temple (Peter), as well as members of the episcopate on Crusader Cyprus (Bishop Fulk of Limassol and Archbishop Eustorg of Nicosia). Some of them siblings were involved in the Fi.h Crusade, the Crusade of the Barons, and the earlier Crusade of King Louis IX of France. >eir niece and nephew respectively found themselves spouses from among the aristocracy of the Latin East (namely Alice, who married John of Caesarea, and Gerald who married Eschiva of Montbeliard), and other members of the family sta.ed high-ranking positions of the clergy in Auvergne (for example another nephew, Bishop Bernard of Le Puy). >is article combines a study of the synchronous Montaigu-family network with that of the diachronic context that saw France’s rise of the Capetians and the crusader states’ steady decline. Utilizing charter evidence from both East and West, chronicles, the genealogies of the crusader aristocracy (namely the so-called “Lignages d’Outemer”), as well as a translation account pertaining to the Holy Passion relic of the “Crown of >orns”, this article shows that the Montaigu-family network was extensive, at times dense enough to control a.airs in the Latin East, and yet overall rather subtle. It demonstrates, furthermore, that those members of the network who were members of the clergy generally subordinated their family’s interests to those of the Latin Church, and that they le. a legacy of ecclesiastical art that can still be seen in Auvergne and Cyprus today, which is evidence of the close links between this family-network from Auvergne and the crusading movement.